A carlactonoic acid methyltransferase that contributes to the inhibition of shoot branching in Arabidopsis - Mashiguchi, Kiyoshi; Seto, Yoshiya; Onozuka, Yuta; Suzuki, Sarina; Takemoto, Kiyoko; Wang, Yanting; Dong, Lemeng; Asami, Kei; Noda, Ryota; Kisugi, Takaya; Kitaoka, Naoki; Akiyama, Kohki; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
SignificanceStrigolactones (SLs) are a group of apocarotenoid hormones, which regulates shoot branching and other diverse developmental processes in plants. The major bioactive form(s) of SLs as endogenous hormones has not yet been clarified. Here, we identify an methyltransferase, CLAMT, responsible for the conversion of an inactive precursor to a biologically active SL that can interact with the SL receptor in vitro. Reverse genetic analysis showed that this enzyme plays an essential role in inhibiting shoot branching. This mutant also contributed to specifying the SL-related metabolites that could move from root to shoot in grafting experiments. Our work has identified a key enzyme necessary for the production of the bioactive form(s) of SLs.